FAM83A and FAM83B as prognostic biomarkers and potential new therapeutic targets in NSCLC - Richtmann, Sarah; Wilkens, Dennis; Warth, Arne; Lasitschka, Felix; Winter, Hauke; Christopoulos, Petros; Herth, Felix; Muley, Thomas; Meister, Michael; Schneider, Marc (Cancers, 2019)
Although targeted therapy has improved the survival rates in the last decade, non-small-cell lung cancer (NSCLC) is still the most common cause of cancer-related death. The challenge of identifying new targets for further effective therapies still remains. The FAMily with sequence similarity 83 (FAM83) members have recently been described as novel oncogenes in numerous human cancer specimens and shown to be involved in epidermal growth factor receptor (EGFR) signaling. Here, gene expression of FAM83A and B was analyzed in a cohort of 362 NSCLC patients using qPCR. We further investigated relations in expression and their prognostic value. Functional assays in NSCLC cell lines were performed to evaluate FAM83A and B involvement in proliferation, anchorage-independent growth, migration, and the EGFR pathway. We observed a highly increased gene expression level of FAM83A (ø = 68-fold) and FAM83B (ø = 20-fold) which resulted in poor survival prognosis (p < 0.0001 and p = 0.002). Their expression was influenced by EGFR levels, pathway signaling, and mutation status. Both genes affected cell proliferation, and FAM83A depletion resulted in reduced migration and anchorage-independent growth. The results support the hypothesis that FAM83A and B have different functions in different histological subtypes of NSCLC and might be new therapeutic targets.
Gesehen am 20.08.2019